Ocular radiation exposure during endoscopic retrograde cholangiopancreatography: a meta-analysis of studies. Issue 4 (April 2019) - Menon, Shyam; Mathew, Ray; Kumar, Mayur
Abstract : Background: The increasing complexity involved in procedures requiring fluoroscopy such as endoscopic retrograde cholangiopancreatography (ERCP) results in heightened screening times with attendant radiation exposure during these procedures. There is increasing awareness of tissue-reactions to the lens of the eye due to radiation exposure, with evidence suggesting that threshold doses may be lower than previously considered. Materials and methods: A literature search was performed to identify studies involving ERCP in which radiation exposure was reported. Demographic data and data on fluoroscopy time and ocular exposure were extracted. Fixed and random-effects meta-analyses were conducted. Results: Twenty-six studies (8016 procedures) were identified, of which 10 studies (818 procedures) contained data on ocular exposure. The mean screening time per procedure was 3.9 min with a mean of three images captured per procedure. On fixed effects meta-analysis, the point estimate for the effective ocular exposure dose per procedure was 0.018 (95% confidence interval: 0.017–0.019) mSv. On random-effects meta-analysis, the effective ocular exposure dose was 0.139 (0.118–0.160) mSv ( Q =2590.78, I 2 =99.5, P <0.001). On comparing these point estimates to the ocular dose limit of 20 mSv/year, 1111 ERCPs (using fixed effects data) and 144 ERCPs (using random-effects data), with a mean of 627 ERCPs/individual/year, could deliver an ocular radiation dose equivalent to this dose limit. Conclusion: Ocular radiation exposures in high-volume ERCP operators (>200 procedures/year) and operators performing complex ERCPs involving prolonged fluoroscopy, need to exercise caution in relation to ocular exposure. Shielding using lead-lined glasses may be reasonable in this group. Abstract : Supplemental Digital Content is available in the text.